Potential Study Of Group Buying Online Shopping Methods In Indonesia - Lea Puspita Wijanto*; Primasatria Edastama (Riwayat: Educational Journal of History and Humanities, 2023)
The Online Group Buying shopping method be an encouragement to start observing group consumption behavior, which will be seen from individual decisions and consumption behavior. The Online shopping method Group buying can be described as a form of quantity discount which is an important part of the online business so that it can encourage increased sales performance and also explore emotional relationships formed by conformity behavior. The purpose of this study was to observe the potential influence of group buying online shopping methods in Indonesia. This research was conducted using variable measurements using the Purposive Sampling method by distributing questionnaires online to 161 respondents. The analysis technique in this study used the Structural Equation Model, with processing techniques and data analysis using SPSS software. The conclusions that can be presented in this study include that cultural influences have a positive effect on conformity behavior, conformity behavior has a positive effect on customer involvement, and has an effect directly or indirectly on online group buying intentions, in addition, the effect of risk moderates the positive relationship between customer engagement and online group buying intentions. In general, for women in Indonesia, the results of this study indicate that the group buying online shopping method can be their main choice for buying behavior.